PROCESS AND SYSTEMS Learning from critical care: Improving intra- and inter-hospital transfer processes in enhanced care and the ward. Issue 3 (2020) - Bonnici, Kathleen; Ridings, Richard; Chinn, Roger; Zwanenberg, Gezz Van; Walsh, Angela; Wigmore, Timothy; Wilkie, Maxine; Davies, Gary
No abstract available